Explore BrainMass

Explore BrainMass

    Functions : Proof by Induction

    This content was COPIED from BrainMass.com - View the original, and get the already-completed solution here!

    Let n be a natural number, and let f(x) = x^n for all x are members of R.

    1) if n is even, then f is strictly increasing, hence one-to-one, on [0,infinity) and f([0,infinity)) = [0,infinity).

    2) if n is odd, then f is strictly increasing, hence one-to-one, on R and f(R) = R.

    Prove that f is strictly increasing by induction.

    © BrainMass Inc. brainmass.com February 24, 2021, 2:15 pm ad1c9bdddf
    https://brainmass.com/math/basic-algebra/functions-proof-by-induction-9458

    Solution Preview

    1.)
    We have to prove:
    f(x) - f(x-1) > 0 for n = even natural number = 2k and x=[0,infinity)
    Step 1:
    x = 1
    f(1) - f(0) = f(1) - f(0) = 1^(2k) - 0^(2k) = 1 ok.

    step 2:
    Let for x >= 1
    f(x) - f(x-1) = x^(2k) - (x-1)^(2k) = m > 0 .....(1)

    step 3:
    to prove,
    f(x+1) - f(x) > 0
    because,
    f(x+1) - f(x) = f(x+1) - m - f(x-1) (from eqn. 1)
    => f(x+1) - f(x) = (x+1)^(2k) - m - (x-1)^(2k)
    => f(x+1)-f(x) =x^(2k) +C(2k,1).x^(2k-1) + ....+C(2k,2k) -m-(x-1)^(2k)

    here, C(2k,r) = ...

    Solution Summary

    A function is proven by induction to not be strictly increasing.

    $2.19

    ADVERTISEMENT